Preparation of Biosorbent from Eucalyptus Trees and its Application for Removal of Some Pollutants in Water - Suad Alshiteewi (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Waste water largely possess organic and inorganic materials such as dyes. Over the years the use of dyes has increased and is immensely used in industries like in various kinds of the textile, paper, leather, food processing, cosmetics, rubber, printing and dye manufacturing industries. Even small quantities of dyes can color large water bodies, which not only affect aesthetic merit but also causes many significant problems such as increasing the toxicity and chemical oxygen demand of the effluent, and also reducing light penetration, which has a derogatory effect on photosynthetic phenomena. The objective of this study is to obtain anew natural biosorbent available in our environment and work to modify its physicochemical properties and that using by low cost- effective technique to enhance its adsorption capacity. Methods. Various parameters like initial dye concentration, PH, temperature and time of agitation were studied. The kinetic and thermodynamic of the crystal violet (Cr.V) sorption onto Eucalyptus biosorbents was studied. Results. Eucalyptus biosorbents was successfully prepared by heating treatment. The plot yield perfect linear curves and the removal rates of Cr.V using eucalyptus biosorbent were increased with increasing Cr.V concentrations. Conclusion. The Eucalyptus biosorbents were found highly efficient for the removal of crystal violet dye at PH 6-7 from aqueous solution and wastewater.